Associations of physical activity with cognitive function and daily physical function among Chinese individuals with heart disease: A cross-sectional study - Dong, Xiaosheng; Yi, Xiangren; Jia, Ningxin; Ding, Meng; Zhou, Yanan; Tian, Caijun (Frontiers in Public Health, 2022)
Background: To investigate the associations between different dimensions of physical activity (PA), cognitive function, and daily physical function in Chinese individuals with heart disease. Materials and Methods: This study included 2792 individuals from the China Health and Retirement Longitudinal Study conducted in 2015. PA was divided into vigorous PA (VPA), moderate PA (MPA), and light PA (LPA). Linear and logistic regression models were established to assess the associations among the indicators. Results: Compared with taking no PA, MPA and VPA at a frequency of 6-7 d/w had lower risks of impaired daily physical function (OR= 0.47, 95% CI: 0.25, 0.91; OR= 0.57, 95% CI: 0.37, 0.88) and higher cognitive function scores (β=1.22, 95% CI: 0.42, 2.03; β=1.08, 95% CI: 0.43, 1.73), while VPA at 3-5 d/w had lower cognitive function scores (β=-1.96, 95% CI: -3.51, -0.40). LPA with a duration of 30-119 min/d had a lower risk of impaired daily physical function (OR=0.59, 95% CI: 0.36, 0.97). MPA and VPA of 30-119 min/d had higher cognitive function scores (β=1.43, 95% CI: 0.49, 2.37; β=1.30, 95% CI: -0.56, 2.06). The 1800-2999 METs had the lowest risks of impaired daily physical function and the highest cognitive function scores (OR=0.18, 95% CI: 0.04, 0.75; β=2.94, 95% CI: 1.67, 4.21). Conclusion: MPA and LPA may be beneficial to cognition and daily physiological functions, while VPA may be related to low cognition, but high-quality research is necessary to prove causality.